PEMBERDAYAAN KADER DALAM UPAYA PENINGKATAN PENGETAHUAN DAN SOSIALISASI PENCEGAHAN STUNTING DI WILAYAH KERJA PUSKESMAS SRI KUNCORO KABUPATEN BENGKULU TENGAH - Tedy Febriyanto; Jon Farizal; Putri Widelia W; Evi Fitriyani; Yunita Yunita (Bajang Institute, 2023)
Background: Stunting is defined as a condition where the body is short or very short based on the Body Length by Age (PB/U) or Body Height by Age (TB/U) index with a threshold (z-score) between -3 SD up to < -2 SD (Olsa, Sulastri, & Anas, 2017). The incidence of stunting can be influenced by various factors, including a lack of macronutrient intake such as energy, protein and fat. However, the intake of micro minerals such as zinc and iron also needs to be considered (Losong & Adriani, 2017). Based on the results of the 2018 Basic Health Research (Riskesdas), stunting in Bengkulu was recorded at 27.98 percent. These figures show that 1 (one) out of 3 (three) children in Bengkulu suffer from stunting in a number of districts or cities (Bengkuluprov, 2021). Methods: There are three steps in this community service, namely preparation, implementation, evaluation and monitoring. It is hoped that this activity can increase public knowledge about preventing stunting, and move people to live healthy lives. Results: A team has been formed that has been given knowledge about stunting, information about stunting prevention and information about laboratory examinations that support stunting examinations consisting of cadres in each village and posyandu Conclusion: Cadre Empowerment Program to increase knowledge and socialize stunting prevention in the Puskesmas Work Area Sri Kuncoro, Central Bengkulu Regency is running well.Outcomes and Achievement Targets: This activity is expected to increase public knowledge about efforts to prevent stunting, and move people to live healthy lives.